Phase analysis, mechanical properties and in vitro bioactivity of graphene nanoplatelet-reinforced silicon nitride-calcium phosphate composites - Bozkurt, Dilan; Akarsu, Melis Kaplan; Akin, Ipek; Goller, Gultekin (Informa UK Limited, 2021)
The aim of this study is to produce highly dense Si3N4 based composites with good mechanical properties and bioactivity. Si3N4 ceramics without using sintering aids, Si3N4-HA and Si3N4-HA-GNP based composites have been produced by spark plasma sintering (SPS) at temperatures of 1525–1550°C. The effect of reinforcement type and content on the densification behavior, phase analysis, microstructural development, mechanical properties, and in-vitro bioactivity behavior of Si3N4 were systematically investigated. Monolithic Si3N4 that contains a high amount of β-Si3N4 phase (~87 wt%) was produced by nearly full densification (~99%). Hydroxyapatite (HA) was used as a starting powder during the preparation of binary and triple composites to provide bioactivity to Si3N4, and after sintering, HA transformed into tricalcium phosphate (β-TCP and α-TCP) polymorphs. The incorporation of GNPs had a positive effect on the stability of β-TCP phases at higher sintering temperatures. The improvement in indentation fracture toughness of the samples with GNP reinforcement was mainly attributable to pull-out and crack deflection mechanisms. In-vitro bioactivity of GNP added composites enhanced with increasing α-TCP content. More calcium phosphate-based particle formation was observed in Si3N4-HA-GNP composites compared to the Si3N4-HA.
Keywords: TP785-869; silicon nitride; bioactivity; graphene; Clay industries. Ceramics. Glass; tricalcium phosphate; spark plasma sintering